Cymru am byth? - Snicker, J; Snicker, Jonathan G.C. (1996)
﻿ This thesis is an attempt to document and explain the manifest changes that have been taking place in Welsh identity since 1979, and the political consequences thereof. It is presupposed that before any autonomist outbursts and other, related political changes take place in a sub-national region such as Wales, some sort of identive change has to occur. This 'identive change' is posited to take place in two stages - identity transformation followed by identity mobilisation. Central chapters deal with this process in two, non-exclusive, dimensions - institutions and individual agents. Alongside institution-building, certain policy areas are deemed to be of crucial importance in relation to the maintenance and dissemination of Welsh identity, namely education and broadcasting. In addition, the relationship between endogenous and exogenous forces affecting Welsh identity is considered in the context of civil society, political praxis, the economy and the European Union. These events are charted and analysed by means of primarily qualitative techniques which emphasise the importance of the positional and strategic confluence of individual 'gatekeepers', who are able to influence policy and, perhaps more importantly, affect the perception and reception of new ideologies and institutional exigencies.